La Biennale di Venezia : always a little further. - Biennale Venetië 2005; Arakistain, Xabier; Araujo, Walo; Baeza, Pepe; Bourgeois, Louise; Cazali, Rosina; Croff, Davide; Dean, Stephen; Fogle, Douglas; Gioni, Massimiliano; Guerrilla, Girls; Hincapié, Maria Teresa; et al. (Venezia : La Biennale di Venezia, 2005)
Albarracin, Pilar ; Allora & Calzadilla ; Amer, Ghada ; Assaël, Micol ; Beckett, Samuel ; Belem, Laura ; Berksoy, Semiha ; Blue Noses ; Bock, John ; Bourgeois, Louise ; Bowery, Leigh ; Büchel, Christoph ; Conlon, Donna ; Dean, Stephen ; Durham, Jimmie ; Eliasson, Olafur ; Esposito, Bruna ; Galindo, Regina ; Garaicoa, Carlos ; Guerrilla Girls ; Gupta, Subodh ; Hatoum, Mona ; Hernández, Diango ; Hincapié, Maria Teresa ; Islam, Runa ; Jacir, Emily ; Kimsooja ; Koolhaas, Rem ; Kulik, Oleg ; Mori, Mariko ; Motti, Gianni ; Museum of American Art Berlin ; Navridis, Nikos ; Neuenschwander, Rivane ; Nguyen-Hatsushiba, Jun ; Nicolai, Olaf ; Paci, Adrian ; Rodero, Cristina Garcia ; Sangar, Bülent ; Schneider, Gregor ; Searle, Berni ; Sierra, Santiago ; Sikander, Shahzia ; Soares, Valeska ; Tahimik, Kidlat ; Tayou, Pascale Marthine ; The Centre of Attention ; Varga Weisz, Paloma ; Vasconcelos, Joana ; Vega, Sergio
La Biennale di Venezia 2005, Venezia, 2005-06-12 tot 2005-11-06
boek